Komunikasi Keluarga Dan Salah Laku Remaja - Roslina, Bakar (1998)
Family communication is a crucial dimension in children development. Adolescence is when physiological, emotional and cognitive changes began their perplexing combination. Role change from children to would be adults adds complexities to their message interpretation process. The purpose of this study was to find out whether there is any relationship between family communication dimensions and juvenile delinquency. Open communication which allows expression of opinions and feelings, control communication meant to seek conformation to parental authority and communication conflict were the three communication dimensions studied. Parent-adolescent communication conflict evolves from the interpretation of message among family members and usually never forgotten without it being resolved. The sample consisted of 328 students (form 1,2,4, and lower six) from six secondary schools in Jitra, Kedah Darul Aman with a ratio of 149 boys and 179 girls. Quantitative method was used using Family Communication Pattern (Ritchie,l991), Communication Conflict item designed by the researcher with 4 questions from Cernkovich and Giordano (1987). Family Related Items and Self-reported Delinquency (Elliot, Delbert & Ageton, 1980) checklist. Findings showed that family communication conflict could be the main indicator towards delinquent behaviour for both gender. Communication patterns do not show any significant direct relationship with juvenile delinquency for boys but open communication shows a significant negative relationship with delinquency for girls. These suggest that intervention for delinquent behaviours could be done through family communication conflict management. Open communication in the family could reduce communication conflict and delinquency among girls. For boys, complexities exist since balancing open and control communication still needs further study.